Standardization of Toad in the Dosage Unit Chorionic Gonadotropin - Roe Gómez, Carlos (1951)
The dosage Chorionic Gonadotropin, following the technique of Mainini Galli, is a simple and quick laboratory test, others whose clinical significance is emphasized. To perform the dosoie Chorionic Gonadotropin, following the above technique, it is necessary to know the minimum dose capable of producing positive biological response in the male toad. 1 The values ​​given in this figure, the different authors vary, and this variation is due to: a) At the low number of animals used. b) the different techniques employed. c) For the different patterns used. d) In the absence of a threshold value. We have tried to eliminate this potential error, to determine the Frog Macho (Bufo spinolosus limensis) of Lima and vicinity, the minimum dose capable of producing positive biological response using 420 animals, using as standards all commercial products Gonadotropin Chorionic that there are exactly square and Galli Mainini technique. Analyzing the results obtained on a statistical basis, applying the concepts developed by JH Gaddum and suggest defined as the minimum dose that can produce positive biological response in 50% of the experimental population. We suggest you take this as a threshold value defining the Toad Unit as "the minimum dose capable of producing positive biological response in 50% of the experimental population." We found that the toad (US) in Bufo spinolosus limensis Lima Area Unit is equivalent to 31 International Units (IU) for hormones gonadotropic Chorionic of human origin and 73 International Units (IU) for hormones gonadotropic chorionic of equine origin. We developed a mathematical graph-simple and practical method to quickly find the value of the Toad (US) Unit and at the same time makes it possible to determine the origin and equivalence chorionic gonadotropin hormone any. We suggest that this method the value of the Toad (US) future determinations Unit is used, using a standard preparation of Chorionic Gonadotropin as recommended by the Committee of the League of Nations.